2008
DOI: 10.2217/14622416.9.11.1647
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Cannabinoid Receptor 1 ( CNR1 ) is Associated with Derangements in Lipid Homeostasis, Independent of Body Mass Index

Abstract: Aims In humans, genetic variation in endocannabinergic signaling has been associated with anthropometric measures of obesity. In randomized trials, pharmacological blockade at the level of the cannabinoid receptor 1 (CNR1) receptor not only facilitates weight reduction, but also improves insulin sensitivity and clinical measures of lipid homeostasis. We therefore tested the hypothesis that genetic variation in CNR1 is associated with common obesity-related metabolic disorders. Materials & methods A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 35 publications
9
51
0
Order By: Relevance
“…Our data are in accordance with most other previous studies (SupplemenTary Table 1 [34,35]) and suggest that genetic variation in the CNR1 gene may have only a very modest effect on the development of human obesity. We are aware that the statistical power of our study is limited owing to small sample size.…”
Section: Discussionsupporting
confidence: 93%
“…Our data are in accordance with most other previous studies (SupplemenTary Table 1 [34,35]) and suggest that genetic variation in the CNR1 gene may have only a very modest effect on the development of human obesity. We are aware that the statistical power of our study is limited owing to small sample size.…”
Section: Discussionsupporting
confidence: 93%
“…CNR1 is considered to be important for modulating weight gain as evidenced by the effect of CNR1-antagonist rimonabant, which has been shown to foster weight loss both in animal studies as well as in clinical trials on humans. Genetic polymorphisms in the CNR1 gene have been associated with basal metabolic index, obesity and various metabolic parameters (Aberle et al, 2007;Baye et al, 2008;Benzinou et al, 2008;Gazzerro et al, 2007;Jaeger et al, 2008;Peeters et al, 2007;Russo et al, 2007), however some negative studies have also been reported (Aberle et al, 2007;Lieb et al, 2009;Muller et al, 2007). Significant association of polymorphisms in CNR1 with anorexia nervosa and bulimia nervosa have also been reported (Monteleone et al, 2009;Siegfried et al, 2004), despite one negative report (Muller et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Despite some conflicting results, CNR1 variants have been associated with metabolic syndrome [89] and dyslipidemia [90], whereas a FAAH 385 A/A missense polymorphism was associated with overweight and obesity [91,92]. Carriers of this polymorphism have increased circulating AEA and related N-acylethanolamine levels [93], and show greater reward-related ventral striatal reactivity [94].…”
Section: The Ecs and Human Obesitymentioning
confidence: 99%